Acute myocardial infarction and concomitant acute intracranial hemorrhage: clinical characteristics and outcomes. (20th July 2022) - Cao, Xiangqi; Wei, Meng; Tang, Manyun; Jian, Zhijie; Liu, Hui; Yue, Xin; Luo, Guogang; Sun, Chaofeng; Guo, Fengwei
Abstract : This study aimed to evaluate the demographic and clinical characteristics, treatments and outcomes of concomitant acute myocardial infarction (AMI) and acute intracranial hemorrhage (ICH). All patients diagnosed with concomitant AMI and acute ICH admitted to our institution were included retrospectively. The patient demographics, clinical characteristics, neuroimaging and treatment approaches were analyzed, and the outcomes of interest included disability as defined by the modified Rankin Scale (mRS) score and all-cause mortality within 1 year of follow-up. Of a total of 4972 patients with AMI, 8 patients (0.2%) with concomitant acute ICH were recruited for the study, including ST-segment elevation myocardial infarction (STEMI, 5 cases) and non-STEMI (3 cases). New-onset acute ICH in 4 of the 5 patients (80%) occurred within 24 hours after the AMI event, and all these patients had a sudden decrease in the level of consciousness, with an average decrease of 4.6 on the Glasgow Coma Scale. All 5 out of 8 patients had irregular shapes and uncommon sites of hematoma presentation documented on CT scans. Unfortunately, 2 patients died from a progression of ICH within 1 week, and 2 of the 6 survivors had poor functional outcomes (mRS ≥3) at the 1-year follow-up. Concomitant acute ICH and AMI are rare complications displaying unique iconography. Acute ICH caused serious prejudice in AMI with higher mortality and poor functional outcomes, and cardiac catheterization without the administration of antithrombotic or antiplatelet agents was feasible for patients who had unstable hemodynamics or STEMI.